Orphans As Mustahik Of Zakat in Sipirok District Tapanuli Regency South: A Study Of The Sociology Of Law - Ilham Dani Siregar (AT-TAFAHUM: Journal of Law, 2017)
Zakat is an obligation for every Muslim who has a purpose and objective.to share with those who are less fortunate. From a social perspective, zakat is prescribed with the aim of eradicating poverty and destitution among Muslims, so that Allah SWT. makes rules and provisions in the distribution of zakat such as the time and amount of zakat that must be paid. Allah also determines the people who are entitled to receive zakat, so that the zakat is right on target and to avoid errors in its distribution as happened in Sipirok District, South Tapanuli Regency. Muzakki makes orphans as mustahik zakat and even prioritizes them over mustahik zakat mentioned in the Quran. How is the implementation and what are the factors causing the Muslim community in Sipirok District, South Tapanuli Regency to make orphans as mustahik zakat and even prioritizes them over other mustahik zakat.